21.6k views
0 votes
For which expression is the sum of the constants greater than the sum of the coefficients?

7+3x^2+7x+3
7+4x^2+4x+1
8+4x^2+8x+2
8+3x^2+7x+4

User Tanatach
by
5.3k points

1 Answer

3 votes

Answer:


8+3x^2+7x+4

Explanation:

The first expression is


7+3x^2+7x+3

The sum of the constants is 7+3=10

The sum of the coefficients is 3+7=10

The second expression is;


7+4x^2+4x+1

The sum of the constants is 7+1=8

The sum of the coefficients is 4+4=8

The third expression is;


8+4x^2+8x+2

The sum of the constants is 8+2=10

The sum of the coefficients is 4+8=12

The fourth expression is;


8+3x^2+7x+4

The sum of the constants is 8+4=12

The sum of the coefficients is 3+7=10

Hence the correct choice is the expression in which the sum of the constants greater than the sum of the coefficients

User Yogesh Malpani
by
5.1k points